Physical activity is reduced prior to ventricular arrhythmiasin patients with a wearable cardioverter defibrillator - Burch, Ashley E.; D'Souza, Benjamin; Gimbel, J. Rod; Rohrer, Ursula; Meng, Tsuyoshi Masuda; Sears, Samuel F.; Scherr, Daniel (My University, 2019)
The utility of accelerometer‐based activity data to identify patients at risk of sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) has not previously been investigated. The aim of the current study was to determine whether physical activity is associated with manifesting spontaneous sustained VT/VF requiring emergent defibrillation in patients with an ejection fraction of ≤35%.